Association of the TP53 Codon 72 Polymorphisms with PCOS Female Infertility in Karbala City - Inam Joudah Radhi; Abdulmutalb Badr Manhy Alkhaleeli; Hameedah Hadi AbdulWahid (Indian Journal of Forensic Medicine & Toxicology, 2021)
To training the association of polycystic ovaries with p53 and 72 polymorphisms in the population offemale infertility in central Karbala and to search for possible interaction with the polymorphism. TheIraqi environment was suffered from acts of profanation by due to wars in Iraq, since 1990 and after 2003,An enormous number of damages and deaths were affected by destructive chemicals and radioactiveresources. These events resulted in either cancer or infertility. Infertility is one of the medical, social andpsychological burdens in Iraqi society. After 12 months or more of failure to a clinical pregnancy lead to aregular unprotected sexual intercourse.